The Bible knowledge of the world is transmitted from father to son (Confluenţe Bibliologice, 2026)
The article is about the Bible - the Book of knowledge and wisdom, pro- phecy and history of mankind from the very beginning. The Bible is the book that should be read and studied by every living on the Earth, for out of it you learn how to use your life to be saved.  The Bible may be considered a General Code of human life.
Keywords: Christian education; The Bible